From the given system, we can observe that the y intercepts of the equations are 3 and -1 respectively.
Also we can find the x intercepts by replacing y for 0 and solving for x:
![\begin{gathered} 0=-3x+3 \\ -3=-3x \\ x=(-3)/(-3) \\ x=1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/xsr8anpj0bed616xqzloyhc0clkm7iqvd5.png)
![\begin{gathered} 0=-x-1 \\ 1=-x \\ x=-1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/n8stqffaohhi8wg2tnsk60f8rdu4ldt618.png)
It means that the x intercepts of the lines are 1 and -1 respectively.
Using these points we can graph both lines, this way:
According to this graph, the intersection of these lines is at (2, -3). This represent the solution of the system, therefore, the solution of the system is x=2 and y=-3.